Inhibitors of the ubiquitin proteasome system block myofibril assembly in cardiomyocytes derived from chick embryos and human pluripotent stem cells. Issue 10 (24th May 2022) - Wang, Jushuo; Fan, Yingli; Wang, Chenyan; Dube, Syamalima; Poiesz, Bernard J.; Dube, Dipak K.; Ma, Zhen; Sanger, Jean M.; Sanger, Joseph W.
Abstract: Details of sarcomeric protein assembly during de novo myofibril formation closely resemble myofibrillogenesis in skeletal and cardiac myocytes in birds, rodents, and zebrafish. The arrangement of proteins during myofibrillogenesis follows a three‐step process: beginning with premyofibrils, followed by nascent myofibrils, and concluding with mature myofibrils (reviewed in Sanger et al., 2017). Assembly and maintenance of myofibrils in living muscle cells. In: Handbook of experimental pharmacology, 2017 [pp. 39–75]. Our aim is to determine if the same pathway is followed in human cardiomyocytes derived from human inducible pluripotent stem cells. We found that the human cardiomyocytes developed patterns of protein organization identical to the three‐step series seen in the model organisms cited above. Further experiments showed that myofibril assembly can be blocked at the nascent myofibril by five different inhibitors of the Ubiquitin Proteasome System (UPS) stage in both avian and human cardiomyocytes. With the exception of Carfilzomib, removal of the UPS inhibitors allows nascent myofibrils to proceed to mature myofibrils. Some proteasomal inhibitors, such as Bortezomib and Carfilzomib, used to treat multiple myeloma patients, have off‐target effects of damage to hearts in three to 6 % of these patients. These cardiovascular adverse events may result from prevention of mature myofibril formation in the cardiomyocytes. In summary, our results support a common three‐step model for the formation of myofibrils ranging from avian to human cardiomyocytes. The Ubiquitin Proteasome System is required for progression from nascent myofibrils to mature myofibrils. Our experiments suggest a possible explanation for the cardiac and skeletal muscle off‐target effects reported in multiple myeloma patients treated with proteasome inhibitors.